2013
DOI: 10.1371/journal.pone.0056916
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Co-Trimoxazole for Treatment and Prevention of Plasmodium falciparum Malaria: A Systematic Review

Abstract: IntroductionCotrimoxazole (CTX) has been used for half a century. It is inexpensive hence the reason for its almost universal availability and wide clinical spectrum of use. In the last decade, CTX was used for prophylaxis of opportunistic infections in HIV infected people. It also had an impact on the malaria risk in this specific group.ObjectiveWe performed a systematic review to explore the efficacy and safety of CTX used for P.falciparum malaria treatment and prophylaxis.ResultCTX is safe and efficacious a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 89 publications
3
61
0
Order By: Relevance
“…Daily co‐trimoxazole prophylaxis may also be considered for children travelling to countries with a high prevalence of bacterial infections and/or malaria, irrespective of their CD4 count/percentage and current treatment status 6, 24, 30, 31. The use of co‐trimoxazole in this context may also have additional benefit as antimalarial prophylaxis 32, although specific malaria prophylaxis appropriate to the regions being visited should always be prescribed.…”
Section: Prophylaxis Against Opportunistic Infectionsmentioning
confidence: 99%
“…Daily co‐trimoxazole prophylaxis may also be considered for children travelling to countries with a high prevalence of bacterial infections and/or malaria, irrespective of their CD4 count/percentage and current treatment status 6, 24, 30, 31. The use of co‐trimoxazole in this context may also have additional benefit as antimalarial prophylaxis 32, although specific malaria prophylaxis appropriate to the regions being visited should always be prescribed.…”
Section: Prophylaxis Against Opportunistic Infectionsmentioning
confidence: 99%
“…A cross-sectional analysis of observational data in Malawi found that daily CTX was associated with reduced malaria parasitaemia and anaemia compared to IPTp-SP among HIV-positive pregnant women [19]. However, while CTX was found to be effective in preventing clinical malaria [20,21], long-term efficacy relative to standard IPTp-SP, toxicity, and birth outcomes associated with CTX have not been established in trials [22]. Many national guidelines still recommend a mix of IPTp-SP and CTX because of past WHO guidelines that recommended IPTp-SP, and because imperfect adherence to daily CTX may put women at risk compared with only 3 doses of IPTp-SP [23].…”
mentioning
confidence: 99%
“…15,20 Not unexpectedly, our study shows that the presence of infection with P. falciparum at inclusion is associated with the low CD4 + T cell counts, themselves primarily related to the concurrent HIV infection, as well with the absence of any previous anti-malarial preventive treatment (IPTp), both of which lead to a stronger likelihood that pregnant women have plasmodial infections (Tables 1-3). Nevertheless, it should be stressed in this context that our sample size is small, and that some of our data only revealed trends that show borderline significance.…”
Section: Discussionmentioning
confidence: 74%